Google search by image : a system evaluation of adjusted images for the detection of visual plagiarism - VAN HEERDEN, L.; DUMINY, S.I.; LUWES, N.J. (Journal for New Generation Sciences, 2015)
This paper investigates the precision of Google™'s Search by Image (SBI) system which lecturers can use to establish a workflow that will combat visual plagiarism in photography programmes. Currently no efficacious visual plagiarism detection method exists for implementation by photography lecturers. Content-based image retrieval systems like Google™ SBI have not yet been tested systemically for the detection of visual plagiarism. Using the Precision method to calculate the accuracy of the system, 300 images were randomly sampled through Google™ Images and altered with different adjustments. The images were uploaded to Google™ SBI and the results indicated a system of high quality.
Published Article
Keywords: photography education; image plagiarism; visual plagiarism detection; Google™ Search by Image; content-based image retrieval